A representation theorem for the linear quasi-differential equation (py′)′+qy=0. (15th April 2000) - O'Hara, J. G.
Abstract : We establish a representation forq in the second-order linear quasi-differential equation( p y ′ ) ′ + q y = 0 . We give a number of applications, including a simple proof of Sturm's comparison theorem.